Kajian Praktis Peningkatan Hasil Belajar IPA dengan Menggunakan Model Learning Cycle 5E - Mustika, Dea (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2017)
This study began with a preliminary study that found the learning outcomes of students in science learning was weak. This was due to teachers who only teach the concepts and theories to students, so that students were not active during learning. Science learning was a learning that aims to develop students' thinking skills to solving a problem. An appropriate learning model was needed to the goals in the science lesson could be achieved well. In this study proposed Learning Cycle 5E model as an alternative learning model that could be used to improve learning outcomes in science learning. Learning Cycle 5E model was a model consisting of 5 stages, which if each stage was implemented it could help achieve the learning objectives. This type of research was a Classroom Action Research that consists of two cycles and was carried out collaboratively between researchers and obsevers. Subjects in this study were teachers and students in V grade. The data obtained were analyzed using qualitative data technique and quantitative data technique. The final result of research in each cycle had increased, both in terms of perencanaa, implementation and learning outcomes. Thus it could be concluded that the Learning Cycle 5E model helped to improve student learning outcomes in science learning.